Vehicle Suspension Systems and Electromagnetic Dampers - Kashem, Saad (Springer Tracts in Mechanical Engineering,, 2018)
This book describes the development of a new analytical, full-vehicle model with nine degrees of freedom, which uses the new modified skyhook strategy (SKDT) to control the full-vehicle vibration problem. The book addresses the incorporation of road bank angle to create a zero steady-state torque requirement when designing the direct tilt control and the dynamic model of the full car model. It also highlights the potential of the SKDT suspension system to improve cornering performance and paves the way for future work on the vehicle's integrated chassis control system. Active tilting technology to improve vehicle cornering is the focus of numerous ongoing research projects, but these don't consider the effect of road bank angle in the control system design or in the dynamic model of the tilting standard passenger vehicles. The non-incorporation of road bank angle creates a non-zero steady state torque requirement.